Virtual worlds and metaverse platforms new communication and identity paradigms - Zagalo, Nelson; Morgado, Leonel; Boa-Ventura, Ana (Premier reference source, 2012)
"This book presents foundational research, models, case studies and research results that researchers and scholars can port to their own environments to evolve their own research processes and studies, covering scenarios of intellectual disciplines and technological endeavors in which metaverse platforms are currently being used and will be used" - Provided by publisher